TV EXCELSIOR Do pioneirismo ao confronto com a ditadura militar e o esquecimento - BONVENTTI, RODOLFO CARLOS (2019)
This thesis investigate the reasons why Excelsior TV, channel 9 in Sao Paulo, launched in 1960, succumbed ten years later, being overlooked when the history of Brazilian television is mentioned these days. The goal is to reconstruct the TV channel’s path and evaluate in which political, economic and social conditions its glory became a nightmare, contributing also to a better understanding of the media in the 60’s in Brazil. This study begins with the analysis of texts and academic, documental, historical and journalistic resources, as well as in-depth interviews with professionals that experienced this period. The results lead to a rescue of the history of the first TV channel to show an unprecedented professionalism in the Brazilian television. Through mostly in-depth interviews, we point to the reasons that took it to advocate a position notably constitutionalist and defy the military regime implemented in 1964. We seek to understand the dynamics of the relations between media and the authoritarianism of the military regime. We bring to light how the rising of Globo Television, which became an example of state-of-the-art TV network, took the role in history that should be Excelsior TV’s by merit and justice.